Kinetics of anticrossing between slip traces and vicinal steps on crystal surfaces. (15th August 2019) - Coupeau, C.; Kazantsev, D.M.; Drouet, M.; Alperovich, V.L.
Abstract: The interaction between vicinal atomic steps and slip traces – straight monatomic steps produced on a crystal surface by the emergence of dislocations – is experimentally investigated and compared to Monte-Carlo simulations. Near the point of apparent crossing between a vicinal step and a slip trace, a checkered three-level surface relief configuration is formed, with two new combinatory steps that borders the opposite highest and lowest terraces. This configuration is unstable with respect to an anticrossing effect which consists in the formation of a nanometer scale bridge that separates the regions with the highest and lowest levels and connects the opposite regions of equal level. It is shown that such an anticrossing effect is a general phenomenon observed on various crystal surfaces, from metals to semiconductors. The anticrossing kinetics was experimentally investigated on the Au(111) surface by scanning tunnelling microscopy under ultra-high vacuum. It is observed that the bridge width increases with time according to the power law with exponent β = 0.45 ± 0.01, i.e. significantly smaller than for the single-particle diffusion ( β = 0.5). Monte-Carlo simulations were performed in order to clarify the involved atomic diffusion mechanisms. In particular, the competition between two microscopic mechanisms of the bridge formation is discussed, i.e., the adatom diffusion along the combinatory steps versus across the bridge from the uppermost to the lowest terrace. Graphical abstract: Image 1